Between Myth and Cure: Group Experience in Narrative Medicine with Neurological Patients - Simona Ghedin; Floriana Caccamo; Francesca Vannini; Maria Rosaria Stabile; Luca Caldironi; Francesca Meneghello; Cristina Marogna (Research in Psychotherapy, 2015)
This research considers the observation of certain parameters within groups formed by patients affected by multiple sclerosis. A music/art therapist and a psychologist/psychotherapist at a neuro-rehabilitation structure in Venice led the groups. Our goal is to assess how the perception of the history of disease can change in patients by using myth and expressive-narrative workshops as a means of trans-formation. The following instruments were administered at the beginning, during, and at the end of the treatment: SCL–90–R, TAS–20, FAT.A.S.–G, and CGQ. Re-sults show a change in patients? perceptions of themselves, both with respect to their disease and to other people. Therefore, myths and their narration appear to be a possible resource that can promote mental transformation processes in an institu-tional neuro-rehabilitative context.